Urgensi Teori Andragogi dalam Memperkuat Visi Moderat Islam di Indonesia - Jasminto Jasminto (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Interpreting andragogic theory as an approach to change a perspective is one effective way that can be used. The principle of moderation which is a perspective and ideology is a unifying tool in diversity, so its existence is absolute in a multicultural country. As a method, andragogy is designed in the form of learning methods, learning objectives, learning evaluations and learning models. A change of perspective becomes an orthientation andragogy that serves as a reification and reflectivity in the success of its learning. Andragogy as a facilitator should be defined as an organized and sustained effort to help adults learn by improving their ability to learn independently. The success of the andragogy is determined by its effectiveness through: learning ability, learning motivation, facilitator in style, ability and teaching methodology. In the andragogy required more to the operational form, the definition of a criteria-based with accurate measurement of the success of learning.